Earnings Management as an Finance Strategy for Company Image - Nurcahyono Nurcahyono; Andwiani Sinarasri (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2023)
Earnings management is a management action performed when a company is experiencing financial distress and during an IPO. Earnings management is carried out so that financial reports always appear to have a positive trend and good prospects. This study aims to empirically examine the various factors that influence earnings management actions by management. This research focuses on financial sector companies listed on the IDX from 2018 to 2022. The sampling method used is purposive sampling with 90 companies and 450 units of analysis (five years). The selected data analysis to test the research hypothesis is multiple linear regression. The research results show that tax planning can be an early warning of earnings management. Audit quality has a positive effect on earnings management. Accounting conservatism and CSR disclosure by the company is a signal that the company does not practice earnings management. Deferred tax expense and institutional ownership variables cannot be used as predictors for detecting earnings management.